Haste makes waste : how curtailed implementation of section 73A of the competition Act 89 of 1998 could derail the aims and policy goals of competition law in South Africa - Van Heerden, C.M. (Corlia) (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.